THE RESPONSIBILITY OF THE LAND TRANSPORTATION COMPANY TOWARDS PASSENGER’S AGGRIEVEMENT DUE TO DELAYS - Rizky Aulia Fitri; Darmawan Darmawan; Teuku Saiful (Kanun Jurnal Ilmu Hukum, 2022)
This article examines the liability of land transportation providers for passengers' annoyance resulting from delays. Article 186 of the Traffic Law and Transportation Code obligated every public vehicle to transport passengers following an agreement. In reality, however, there were still businesses that were not meeting their obligations. The purpose of this study was to explain the causes of the delay and the company's liability as a result of the delay. This study employed empirical legal research methods and a sociological law perspective. The study revealed that the terminal operator's management of services was suboptimal, the drivers were unprofessional, the vehicle's engine malfunctioned, and passengers were picked up outside the terminal, but the land transportation companies that caused the delay were not responsible for their passengers and did not offer compensation. This case required the Service Unit Coordinator of the Bus Station in Banda Aceh to be resolute in following up on the Land Transportation Management Center's warnings to revoke the permits of irresponsible companies toward passengers due to their negligence.